2005
DOI: 10.1021/jp045489n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of Pd(II) in Concentrated Nitric and Perchloric Acid Solutions by XAFS

Abstract: XAFS spectra of palladium (II) 2+ square-planar aqua ion in strong perchloric acid, the use of an FEFF6 theoretical approach led to a first-shell Pd-O w distance of 2.00 (1) Å and a Debye-Waller (DW) factor of σ 2 ) 0.0030 (3) Å 2 . Four water molecules are tightly bound to the Pd 2+ ion in the equatorial plane, while two (or one) axial water molecules are weakly bound to the metal ion at 2.5 Å with a DW factor of 0.015 (5) Å 2 . For highly concentrated mixtures (4-6 M HNO 3 ) and for pure concentrated (4-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 27 publications
12
38
0
Order By: Relevance
“…2, also exhibits a bathochromic shift with increase in the concentration of nitric acid due to nitrate complexation. Purans et al [14] studied the structure and speciation of Pd 2+ in nitric and perchloric acid medium. The stability constants for the complexation of palladium (II) ion with nitrate ions in nitric acid medium, derived from solvent extraction data, were reported by Tarapcik [15].…”
Section: Resultsmentioning
confidence: 99%
“…2, also exhibits a bathochromic shift with increase in the concentration of nitric acid due to nitrate complexation. Purans et al [14] studied the structure and speciation of Pd 2+ in nitric and perchloric acid medium. The stability constants for the complexation of palladium (II) ion with nitrate ions in nitric acid medium, derived from solvent extraction data, were reported by Tarapcik [15].…”
Section: Resultsmentioning
confidence: 99%
“…Tarapčik reported stability constants for all nitrato complexes of Pd in Pd II _NASs calculated from the results of solvent extraction experiments . Taking into account the structural data on palladium nitrato complexes, an XAFS investigation of Pd II _NASs was carried out with [HNO 3 ] in the range of 1–6 m …”
Section: Resultsmentioning
confidence: 99%
“…Fitting of the experimental data yields stability constants 1 and 2 , which corrected to ionic strength (I) values of 1.49 and 0.45 for a solution with I = 3 M. [26] Tarapčik reported stability constants for all nitrato complexes of Pd in Pd II _NASs calculated from the results of solvent extraction experiments. [27] Taking into account the structural data on palladium nitrato complexes, an XAFS investigation of Pd II _NASs was carried out with [HNO 3 ] in the range of 1-6 M. [28] While speciation in Pd II _NASs with low to high concentrations of HNO 3 (0.1 up to 6 M) are well studied, no information is available on species distribution in solutions with high HNO 3 contents (> 6 M), where homoleptic nitrato complexes should exist. To cover the widest spectrum of HNO 3 concentrations, NMR spectroscopy on the nuclei of ligand atoms can be very informative.…”
Section: Pd_nassmentioning
confidence: 99%
“…(1) According to a previous report [23], the small peak results from multiple scatterings related to N and distal O atoms in the NO 3 − coordinating to Pd(II) in a unidentate manner. Since the Fourier-transformed spectra of Pd(II) in AMP03 and 7.0 M HNO 3 solution were similar to each other, we concluded that the adsorbed Pd(II) species was coordinated to NO 3 − .…”
Section: Structural Analysis Of Pd(ii) Adsorption By Amp03 By Means Omentioning
confidence: 87%